2019
DOI: 10.12659/msm.916472
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Winter Temperature on Patients with Ischemic Stroke

Abstract: Background The incidence of ischemic stroke increases in winter. This study aimed to explore the effect of winter temperatures on the risk factors, etiology, coagulation, and degree of neurological impairment in patients with ischemic stroke using temperature and rainfall data from the Guangzhou Meteorological Bureau during the winter months of December, January, and February. Material/Methods We divided 112 patients with ischemic stroke into low-temperature and non-low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
3
12
1
Order By: Relevance
“…Presumably, economy-related lifestyle habits rather than genetic factors account for the difference. Some studies have shown that low temperature may contribute to high IS severity [37], [78]. But in our work, change in RH two consequent days before IS was a predictor of severe IS.…”
Section: B Association Of Stroke Severity With Individual and Environ...contrasting
confidence: 66%
“…Presumably, economy-related lifestyle habits rather than genetic factors account for the difference. Some studies have shown that low temperature may contribute to high IS severity [37], [78]. But in our work, change in RH two consequent days before IS was a predictor of severe IS.…”
Section: B Association Of Stroke Severity With Individual and Environ...contrasting
confidence: 66%
“…Cold temperatures could also lead to vasoconstriction and subsequent elevation of blood pressure. In our study, the elevated blood pressure of participants exposed to cold spells was consistent with previous findings (23,30,32). Some thrombogenic factors-such as fibrinogen level, platelet aggregation, blood cell count, and CRP-increase in response to exposure to cold, which increases the risk of brain ischemia (6,15).…”
Section: Discussionsupporting
confidence: 92%
“…The t-test was used for continuous variables with normal distribution and the Mann-Whitney-Wilcoxon test for continuous variables without normal distribution. The Chi-square test was used for categorical variables (23). General linear models were used to analyze the association between extreme temperatures and the continuous variables that were statistically significant in the inter-group comparison.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations